How Elementary Students Communicate Their Mathematical Problem Solving in Writing - Rohmah, Lailatur; Rahayu, Ratri; Fardani, Much Arsyad (Papanda Publisher, 2023)
Mathematics plays a crucial role in education, particularly in the development of problem-solving abilities. The proficiency in mathematical problem-solving has garnered significant attention, especially in light of the low academic performance of Indonesian students in the 2018 PISA assessment. This research aims to analyze the mathematical problem-solving skills of elementary school students using the Polya Method. The study employs a qualitative research design with a phenomenological approach. Subjects were selected through purposive sampling, representing three ability groups. Data were collected through tests, interviews, and observations, and were subsequently analyzed using the qualitative approach of Miles & Huberman. The findings indicate High Category Mathematical Problem-Solving Ability (HPSA) exhibit excellent mathematical problem-solving skills. They can correctly answer all questions, comprehend problems, plan, execute, and review their answers thoroughly. Moderate-ability students (MAT) demonstrate relatively good skills, although they tend to rush through problem-solving and overlook the importance of double-checking. Low-ability students (LAT) encounter difficulties in understanding problems, planning, and implementing solutions. They exhibit less systematic approaches and frequently make errors. The discussion concludes that the understanding of problems, planning, and the implementation of Polya's problem-solving steps need improvement, especially among moderate and low-ability students. Teachers should provide more intensive guidance, particularly in understanding problems and planning solutions. This research provides a profile of students' problem-solving skills and serves as a foundation for the development of more effective mathematics learning strategies in schools.